Reanaliza NCEP/NCAR i możliwości jej wykorzystania do badań rozkładu przestrzennego temperatury powietrza w Arktyce i Subarktyce Amerykańskiej - Vizi, Zsuzsanna; Przybylak, Rajmund (Wydawnictwo Uniwersytetu Marii Curie-Skłodowskiej, 2006)
artykuł z : Annales Universitatis Mariae Curie-Skłodowska, Sectio B, Geographia, Geologia, Mineralogia et Petrographia Vol. 61 (2006), s. 436-445 streszcz. ang. tyt. równol. w jęz. ang. : NCEP/NCAR reanalysis and its usefulness in the study of the spatial distribution of air temperature in the American Arctic and Subarctic artykuł z : Annales Universitatis Mariae Curie-Skłodowska, Sectio B, Geographia, Geologia, Mineralogia et Petrographia Vol. 61 (2006), s. 436-445 streszcz. ang. tyt. równol. w jęz. ang. : NCEP/NCAR reanalysis and its usefulness in the study of the spatial distribution of air temperature in the American Arctic and Subarctic